KLASIFIKASI KELULUSAN MAHASISWA MENGGUNAKAN METODE DECISION TREE MENGGUNAKAN APLIKASI RAPIDMINER - Qittratul Ameliatus; Zaehol Fatah (Jurnal Riset Teknik Komputer, 2024)
Data mining helps to make predictions and helps to provide precise and careful decisions. Classification of student graduation is an important process in the education system. By using classification methods, information can be obtained about the possibility of student graduation based on related variables. This research aims to analyze the classification of student graduation using the Decision Tree method with the RapidMiner application. The data used is student graduation data from 100 students consisting of 50 male students and 50 female students. The variables used are age, gender, grade, course, UTS, UAS, and graduation. The results showed that the Decision Tree method can be used for student graduation classification with a high accuracy of 99.00%. The most influential variables in the classification of student graduation are grades and UTS and UAS.